Variation and Character Association in Taramira (Eruca sativa) - Divakara Sastry, E V; Meena, Braj Kishore (Annals of Arid Zone, 2016)
From the various agroclimatic regions of Rajasthan state 83 accessions of taramira were collected and evaluated with two checks to assess the variability, heritability. genetic advance and correlations. All the characters viz., days to 50% flowering. days to 70% maturity, plant height. primary branches per plant, secondary branches per plant. number of siliquae per plant. siliquae length, number of seed per siliquae. seed )'ield per plant, test weight. biological yield. oil content and harvest index, showed highly significant variability. High heritability (broad sense) values were observed for plant hcight, days to maturity. number of siliquae per plant. primary branches pcr plant and oil contcnt. whereas low heritability was observed for biological yield. Harvest index and sccondary branches per plant showed high genetic advance. although it was very low for days taken to 70% maturity. The seed yield was significantly and positively associated with days to maturity, primary branches per plant. number of siliquae per plant, biological yield and harvest index.